DAMPAK PENGGUNAAN MEDIA SOSIAL YOUTUBE TERHADAP PERILAKU NEGATIF ANAK (Studi Kasus pada SDN 2 SUMBAWA) - Kurniawati, Luthfiyah; Utama, Abdul Alimun (Jurnal Ilmiah Mandala Education (JIME), 2022)
The research objective was to find out and describe the form of using social media youtube in children (a case study on Grade 5 students of SDN 2 Sumbawa). This is to find out and describe the type of information that the children are most interested in (a case study on Grade 5 students of SDN 2 Sumbawa). To find out and describe the impact of using YouTube social media on children's negative behavior (a case study on Grade 5 Students of SDN 2 Sumbawa). Based on the research results, students can depend on technology and communication media. Students tend to do their own assignments with the help of the internet rather than group study. Can affect the relationship because of lack of control from the teacher. Students can freely access all bad websites. Reducing the social nature of  humans because they tend to prefer to connect via the internet or through the media rather than meeting in person. It is likely that students without the Teacher's knowledge can access videos that contain elements of violence and aggressiveness. YouTube social media provides many benefits for life if used wisely, such as helping in the learning process. In addition, the social media youtube among students also has a negative impact, such as making children lazy to learn, feeling dependent on internet communication media and the most dangerous impact of using social media youtube, which is damaging eye health because they look at gadget screens too often, Computers and Television. Therefore, in reducing the impact of using YouTube social media, it is necessary to have supervision from parents and teachers.